Evaluation of surgical outcome in open globe injuries in a tertiary ophthalmological centre - Dahal, Polina; Byenju, RN (Journal of College of Medical Sciences-Nepal, 2014)
Aims: To evaluate the clinical presentations and surgical outcome in patients with open globe injuries in a tertiary ophthalmological centre in Bharatpur Eye Hospital, Bharatpur. Methods: Seventy nine patients with ocular injury who underwent surgery were included in the study. The type of injury, surgical interventions and final visual outcome were recorded. The period of study was from 2012 May to 2013 May. Results: Injury was mild in 48 (60.8 %), moderate in 17 (21.5 %) & severe in 14 (17.7 %) cases (International Ocular Trauma Classification). Forty six (58.2 %) cases had only primary repair, 27 (34.2 %) had associated lens extraction, 12(15.2 % )had vitrectomy, 2 (2.5 %) had retinal detachment surgery, one (1.3 %) had intra-ocular foreign body removal, one (1.3 %) evisceration. Thirteen 16.5 %) cases underwent secondary procedures. Final vision was 6\18 or better in 20 (25.3 %), 6\18-6\60 in 14 (17.7 %) and <6\60 in 15 (18.9 %) cases. 10 (12.7 %) cases developed phthisical changes. Conclusion: Present analysis reveals that open globe injuries can present in varying severity &though the overall prognosis is grave, prompt surgical intervention can result in better visual outcome. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-2, 9-14 DOI: http://dx.doi.org/10.3126/jcmsn.v9i2.9678